Potential of natural biocides for biocontrolling phototrophic colonization on limestone. (February 2016) - Sasso, S.; Miller, A.Z.; Rogerio-Candelera, M.A.; Cubero, B.; Coutinho, M.L.; Scrano, L.; Bufo, S.A.
Abstract: Rocks, either in natural geological outcrops or in stone monuments, are common habitats for a wide variety of microorganisms which colonize both rock surfaces and cracks. Physical properties such as porosity and surface roughness make limestone susceptible to biological colonization, which may induces aesthetic and/or physical and chemical damages. Organisms causing biodeterioration on monuments have usually been controlled by chemical products (biocides). In order to overcome the impact of these substances on the environment, human health and stone substrates, alternative tools such as natural products from plants or microorganisms can be used as an innovative approach for stone conservation. In this work, the efficiency of natural biocides (cells free culture filtrates of Trichoderna harzianum and Burkholderia gladioli, as well as glycoalkaloids from spontaneous Solanaceae ) was tested under laboratory conditions against a multi-species phototrophic culture developing on Hontoria limestone. Their efficiency was assessed by digital image analysis, in vitro chlorophyll a quantification and confocal laser scanning microscopy. These techniques showed a good correlation, revealing that cells free filtrate of Trichoderma harzianum had an antagonistic action against the multi-species phototrophic culture tested in this work. Highlights: We tested the efficiency of natural biocides against a phototrophic culture on limestone. Cells free culture filtrates of Trichoderna harzianum and Burkholderia gladioli were tested. Glycoalcaloids from spontaneous Solanaceae were also tested. Their efficiency was assessed by digital image analysis, chlorophyll a quantification and CLSM. T. harzianum treatment showed an antagonistic action against phototrophic microorganisms.